Google+ marketing for dummies - Stay, Jesse (--For dummies., 2013)
Organize customers, craft targeted messages, or host Hangouts with Google's social networkGoogle+ is Google's social network that has the social media world abuzz with excitement. With Google tools like YouTube, Picasa, Blogger, and Picnik being integrated with Google+, marketers will find Google+ is the best way to reach the long-time users of Google's other tools. Google+ expert Jesse Stay shows you how to create and maximize your Google+ presence to connect with your customers. Explains how to sign up for your account and set up your brand profileShows you how to use Circles, craft targeted messages for the Stream, and add multimedia features to your postsHelps you discover content and the value of the +1 buttonShows you how to be mindful of SEO, so that your Google+ brand page can be foundAddresses using Google+ to launch a product or promote an eventConfidently enter the exciting new Google+ social neighborhood with Google+ Marketing For Dummies.